The Effects of Divalent Cation-Chelated Prion Fibrils on the Immune Response of EOC 13.31 Microglia Cells - Jen, Huan-I (Cells, 2020)
Transmissible spongiform encephalopathies (TSEs) are epidemic neurodegenerative diseases caused by prion proteins; in particular, they are induced by misfolded prion proteins (PrP(Sc)). PrP(Sc) tend to aggregate into insoluble amyloid prion fibrils (fPrP(WT)), resulting in apoptosis of neuron cells and sequential neurodegeneration. Previous studies indicate that microglia cells play an important role in the innate immune system, and that these cells have good neuroprotection and delay the onset of TSEs. However, microglia can be a double-sided blade. For example, both Cu(2+) and Mn(2+) can induce microglia activation and secrete many inflammatory cytokines that are fatal to neuron cells. Unfortunately, PrP have cation binding sites at the N-terminus. When PrP(Sc) accumulate during microglial phagocytosis, microglia may change the phenotype to secrete pro-inflammation cytokines, which increases the severity of the disease. Some studies have revealed an increase in the concentration of Mn(2+) in the brains of patients. In this study, we treated microglia with fPrP(WT) and cations and determined IκBα and IL-1β expression by Western blotting and quantitative polymerase chain reaction. The results showed that Mn–fPrP(WT) decreased IκBα levels and dramatically increased IL-1β mRNA expression. In addition, competing binding between Cu(2+) and Mn(2+) can decrease the effect of Mn–fPrP(WT) on IκBα and IL-1β. The effects of divalent cations and fPrP(WT) in microglia inflammation are also discussed.